Physiological and Pathological Role of Alpha-synuclein in Parkinson’s Disease Through Iron Mediated Oxidative Stress; The Role of a Putative Iron-responsive Element - Olivares, David (Molecular Diversity Preservation International (MDPI), 2009)
Parkinson’s disease (PD) is the second most common progressive neurodegenerative disorder after Alzheimer’s disease (AD) and represents a large health burden to society. Genetic and oxidative risk factors have been proposed as possible causes, but their relative contribution remains unclear. Dysfunction of alpha-synuclein (α-syn) has been associated with PD due to its increased presence, together with iron, in Lewy bodies. Brain oxidative damage caused by iron may be partly mediated by α-syn oligomerization during PD pathology. Also, α-syn gene dosage can cause familial PD and inhibition of its gene expression by blocking translation via a newly identified Iron Responsive Element-like RNA sequence in its 5’-untranslated region may provide a new PD drug target.